The Application of Science and Technology for Regional Development of Edutourism Villages Based on Low Cost Ecotourism Integrated with Science Techno Park - Riana Mayasari; M.Sang Gumilar Panca Putra; Hendra Hadiwijaya; Alfitriani; Rian Rahmanda Putra (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2023)
Tanjung Pinang II Village is located 10 km from the administrative center of Ogan Ilir Regency, Indralaya. Tanjung Pinang II Village can be developed as a tourist area due to the easy access. The problems of to be tourist village is unproductive of potential land, the emergence of noise pollution from blacksmith activities in residential areas, do not have a tourism management master plan; and The absence of basic infrastructure supporting ecotourism-based Edutourism. The solution of this problem is Counseling on Strengthening Human Resources in Edutourism Villages and Revitalizing Non-Productive Multi Sector Integrated Land as well as Cultivation Technique Training, Relocation of Blacksmiths to Integrated Areas and Planting Sound Barrier Plants, Making a Master Plan for Mapping the Development of Integrated Edutourism Areas in Science Techno Park (STP), Building Edutourism Supporting Facilities Based on Low Cost Ecotourism. The solutions offered are in accordance with the background of the expertise. The purpose of PIPK in Tanjung Pinang-II Village is to provide the solutions in the fields of production, management, marketing, infrastructure and the environment. The method of implementing this PIPK is analyzing the situation and conditions of partners, providing solutions to problems, Making Appropriate Technology (TTG) that will be transferred to partners, Training and Mentoring and Evaluation of Implementation of Activities. The results of the service can be concluded that this activity is a solution for Tanjung Pinang II Village to prepare itself as a tourist village.